2020
DOI: 10.1016/j.jmb.2020.02.007
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Editing by CRISPR-guided Excision of 5-Methylcytosine

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 80 publications
0
24
0
1
Order By: Relevance
“…Recently (Taghbalout et al, 2016) used Casilio-ME for RNA-guided editing of 5-mC by targeting TET1 to specific genomic sites, and co-delivery of TET1 and other protein factors, to activate methylation-silenced genes. Similarly, Devesa-Guerra et al (2020) fused the catalytic domain of ROS1 5-mC DNA glycosylase with dCas9 and reported that dCas9-ROS1 (but not the dCas9-TET1) can reactivate methylation-silenced genes by active demethylation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recently (Taghbalout et al, 2016) used Casilio-ME for RNA-guided editing of 5-mC by targeting TET1 to specific genomic sites, and co-delivery of TET1 and other protein factors, to activate methylation-silenced genes. Similarly, Devesa-Guerra et al (2020) fused the catalytic domain of ROS1 5-mC DNA glycosylase with dCas9 and reported that dCas9-ROS1 (but not the dCas9-TET1) can reactivate methylation-silenced genes by active demethylation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Moreover, TET proteins are also able to oxidize thymine to 5-hydroxymethyluracil, thereby introducing another confounding epigenetic mark that produces a unique spectrum of modifications on chromatin structure and transcription factor activity [96]. A recent candidate for the improvement of such a strategy is the fusion of dCas9 to the Arabidopsis ROS1 glycosylase that directly removes 5-methylcytosine by direct base excision repair, foregoing the intermediate oxidized derivatives with epigenetic potential [97]; yet the issue of the overexpression of an enzyme with a capacity for unwanted and non-targeted effects is not solved by this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ROS1 and DME can also work in mammalian systems inducing genome‐wide methylation changes and targeted demethylation (Mok et al, 2017; Parrilla‐Doblas et al, 2017; Morales‐Ruiz et al, 2018). Fusion of the ROS1 catalytic domain to dCas9 successfully reactivated a methylation‐silenced luciferase reporter gene and induced partial demethylation in a replication‐independent manner, although the system has not yet been applied to plants (Devesa‐Guerra et al, 2020).…”
Section: Gene Transcription Control and Epigenome Editingmentioning
confidence: 99%